Rab5c-mediated endocytic trafficking regulates hematopoietic stem and progenitor cell development via Notch and AKT signaling - Heng, Jian; Lv, Peng; Zhang, Yifan; Cheng, Xinjie; Wang, Lu; Ma, Dongyuan; Liu, Feng (PLOS Biology, 2020)
Cell-autonomous Notch signaling regulated by the membrane trafficking protein Rab5c plays an instructive role in hematopoietic stem and progenitor cell specification, while the AKT signaling seems to provide a permissive signal to maintain hemogenic endothelium survival.